The roots of a quadratic equation are given as 6 and 7. This means that x - 6 = 0 and x - 7 = 0

We can write ( x - 6)( x - 7) = 0

=> x^2 - 6x - 7x + 42 = 0

=> x^2 - 13x + 42 = 0

Therefore the required quadratic equation is

**x^2 - 13x + 42 = 0**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now